The Influence of Frequency Fertilization Different to The Biomass and Population Tubifex sp in The System Resirculation - Nanda Rahmania Syafitri; Niken Ayu Pamukas; Rusliadi Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted on 2 september until 23 october 2019 at UPT of seeding laboratory department of aquaculture faculty of fisheries and marine university of riau. The purpose of this research is to know the best frequency of fertilization used quail feces fermentation, tofu waste fermentation and tapioca flour on resirculation system for increase biomass and Tubifex sp population. The method used is completely randomized design (CRD) with 1 factor consisting of 4 treatment levels and 3 replicates (12 unit of tray). Tubifex sp stocking density is used for every media is 10 gr/media, the treatment use frequency seeding each day, each 3 days, each 5 days and each 7 days  with equal seeding dose every media is 45 gr/media. During 52 days maintenance of the best treatment is each 3 days seeding frequency with biomass grows 72,67 gr and population 104.485 ind. Keywords: Tubifex sp, Fermentation, Frequency, Biomass, Population